If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6g + -48 = 102 Reorder the terms: -48 + -6g = 102 Solving -48 + -6g = 102 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '48' to each side of the equation. -48 + 48 + -6g = 102 + 48 Combine like terms: -48 + 48 = 0 0 + -6g = 102 + 48 -6g = 102 + 48 Combine like terms: 102 + 48 = 150 -6g = 150 Divide each side by '-6'. g = -25 Simplifying g = -25
| 5x/8-9=x | | 6m+15=2m+25 | | Y=-6x+11 | | n=2nrh | | 2(x+5)=-3(x-15) | | -4x+1=3x-13 | | 9(7y-5)-(4+2)= | | 1/2(3x-25)=4x | | 2(3y+9)-3(y+3)= | | 4.4q-5.7-4.5q=-1.1q-4.3 | | |2x-5|=11 | | -6(x+3)=7x+34 | | 7x-8=-3x-72 | | 31x87=45 | | 9x^2-237x+78=0 | | 7x+6x+2+9=7x+5+5x | | 2(x+6)=2(10+6) | | -2x^2=-180 | | -2y+6=6(y+5) | | -4y^2-12y+5=0 | | 6(x-7)=9x-18 | | 2x+382=2500 | | 80-25-24=32-1 | | 4u^2+21u=5 | | -7x+20=-2(x+5) | | 1.5/6=8/r | | 6x^3-46x^2+88x=0 | | 9-(-18a)=-1 | | 8(w-8)=3w-14 | | -6n+2n=-8 | | -2x^3-34x^2+76x=0 | | 15/90.5=25/x |